THE EFFECT OF THE CAKE PLATFORM TOWARD STUDENTS’ SPEAKING SKILLS (A Pre-Experimental Research to the First-grade IPS 1 Students at SMAN 1 Peudada) : English - Asmullah, Putra; Zuraini, Zuraini (Journal of English Education and Social Science, 2023)
ABSTRACT The title of this research is the effect of cake platform toward students’ speaking skills (An experimental research to the first grade IPS-1 students of SMAN 1 peudada). The problem of this research 1) is the Cake platform can improve students’ speaking skills of the first-grade IPS 1 students at SAMN 1 Peudada? 2) is the use of the Cake platform effective toward speaking skills of the first-grade IPS 1 students at SMAN 1 Peudada?. The purpose of this research 1) to determine whether or not the Cake platform can improve students’ speaking skills of the first–grade IPS 1 students at SMAN 1 Peudada. 2) to determine whetheror not the Cake platforms effective toward speaking skills of the first grade IPS 1 students at SMAN 1 Peudada. The methodology of this research was a pre-experimental design. The population of this research was SMAN 1 Peudada. The sample of this research was first-grade IPS 1 which consist 28 students in the class. The used of intrument of this research was speaking test and questionnaire. Data were analyzed quantitatively using SPSS Statistics Output, such as the Normality Test and Paired-Sample T-test. Meanwhile, the average pre-test and post-test speaking scores were analyzed differently based on specific objectives. The use of the Cake platform as a medium to improve students' speaking skills is effective, this can be seen from the average post-test reading comprehension score µ = 76.25 higher than the pre-test reading comprehension average score. From the data analysis, the results of the Paired-Sample T-test were 0.000 <0.05 with a significant value if Sig. (2-tailed) < 0.05 means there is a significant difference, with normally distributed data, Asymp. Sig. (2-tailed) = 0.434 on the basis of the Normality Test decision making using the Kolmogorov-Smirnov significance data, if the significance value is > 0.05 then the residual value is normally distributed. Thus, the alternative research hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. It can be interpreted that the influence of the Cake platform as a media for improving students' speaking skills is an effective strategy for students to improve their speaking.